Analisis Motivasi, Sikap, dan Konsep Diri Siswa terhadap Pembelajaran Matematika Kelas VA SD Negeri 40 Pontianak Utara - Angelina, Angelina; Ardimansyah, Ardimansyah; Purnomo, Sheva Readyanda (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Mathematics actually plays an important role in various aspects of life. There are two influential factors in mathematics learning. This research analyzes internal factors that affect mathematics learning, namely motivation, attitude, and students' self-concept because these factors play a significant role in mathematics. This study aims to describe the motivation, attitude, and self-concept of students towards mathematics in class VA at SD Negeri 40 Pontianak Utara. The method used is qualitative research with a descriptive qualitative approach. The population in this study is class VA students, and a sample of seven students was selected using random sampling technique. Data collection in this study was done through observation and interviews. In the data analysis technique, the researcher observed mathematics learning and then conducted interviews, and the results were processed and analyzed. Based on the research findings, it was found that the majority of students in class VA have a significant motivation in mathematics learning, although some other students do not have an interest in learning mathematics. The attitude of class VA students towards mathematics is also quite positive, and they believe that mathematics can help them develop, although there are still students who do not feel progress and are not interested in learning mathematics. Most of the class VA students have understood their self-concept in relation to mathematics learning.